The Use of Housing Policy Instruments in the Process of Investing in the Human Capital of Older Generation. The Example of Poland - Rataj, Zuzanna (Studia z Polityki Publicznej, 2024)
The ageing of societies and the simultaneous decline in births present the majority of European countries with challenges not only regarding the provision of long-term care but also how to use the potential offered by older individuals. The use of housing policy instruments offers a chance to use, and more importantly invest in, the human capital of the older generation. The aim of this article is to demonstrate how implementing housing policy solutions may foster the process of investing in the human capital of both the current and future seniors, as exemplified by Poland. The article fits in socio-economic analyses. The author uses the results of sociological and economic research, both based on foreign sources and own research. The examined problems are presented with the use of desk research and descriptive analysis.